The Application of Video Transcript on Youtube for Students' Reading Literacy - Aulia, Anggita Fitri; Agustina, Eliasanti (Universitas PGRI Adi Buana Surabaya, 2024)
This research investigates students' perspectives on utilizing video transcripts from YouTube videos to enhance student learning, particularly in Reading Literacy. This research used an experimental design with a quantitative approach. The research involved 30 eighth-grade students from junior high schools in Surabaya and Sidoarjo who experienced reading difficulties. The research aimed to explore whether using films with transcribed text on YouTube, known as transcribed video, can improve the reading literacy of grade eight students. The findings from this study showed a significant level of student interest in utilizing transcripts when viewing YouTube videos. As a result, their reading comprehension was also affected by this study. After watching the videos, the students also checked the text transcriptions available on their devices. This research shows that video transcripts are utilized in educational settings and general reading practice outside the traditional classroom environment